الصلابة النفسية لدى المصابين باضطراب الضغط مابعد الصدمة لعينة من عائلات الضحايا كوفيد 19 بمدينة الأغواط - أميمة زنبط; حليمة عبد الرحيم; خديجة دعماش (My University, 2021)
This research aims at identifying the Psychological Hardiness for patients with Post- Traumatic Stress Disorder of a sample of COVID-19 Victims’ families of laghouat city, and the nature of the relationship between the Psychological Hardiness and Post-Traumatic Stress Disorder for COVID-19 Victims’ families. The sample of this research is composed of fifty (50) members (26 males and 24 females) whom were chosen accidentally, under the descriptive analytical approach. In This study, we have used two measures: The Psychological Hardiness measure by Imad Mekheimar, and the Post-Traumatic Stress Disorder measure by Davidson translated to Arabic by Abdel Aziz Thabet. Data were analyzed manually using the following statistical procedures: person’s Correlation Coefficient, Alpha Cronbach’s coefficient, Arithmetic mean, The Hypothetical mean, independent simple T test, one simple T testand One-Way Analysis of Variance. Finally, we have reached the following results: -There is an inverse relation between the Psychological Hardiness and the PostTraumatic Stress Disorder for the COVID-19 Victims’ families of laghouat city. -COVID-19 victims’ families of Laghouat city have a high level of Psychological Hardiness.‌د - There is no dominant standard among the Psychological Hardiness standards of COVID-19 Victims’ families of laghouat city. - COVID-19 victims’ families have a low level of Post-Traumatic Stress Disorderof COVID-19 Victims’ families of laghouat city. -There is no dominant standard among standard the Post-Traumatic Stress Disorder standards of COVID-19 Victims’ families of laghouat city. -There exist differences between the sexes concerning the level of Psychological Hardiness of COVID-19 Victims’ families of laghouat city. -There is no differences between the sexes concerning the level of PostTraumatic Stress Disorder of COVID-19 Victims’ families of laghouat city. - There is no differences between the sexes in the standards of the Psychological Hardiness of COVID-19 Victims’ families of laghouat city. - There is no differences between the sexes in the standards of the PostTraumatic Stress Disorder of COVID-19 Victims’ families of laghouat city(Psychological Hardiness), (Post-Traumatic Stress Disorder), (COVID-19Victims’ families